Sosialisasi Hukum Pencegahan Perundungan di SMA Negeri 2 Slawi - Moh Taufik; Sugiyanto Sugiyanto; Soesi Idayanti; Evy Indriasari; Sanusi Sanusi; Moh. Wildan (Institut Teknologi dan Bisnis Semarang, 2026)
The practice of bullying is an act of exercising dominance to inflict harm upon others through verbal abuse, physical violence, or psychological pressure, which ultimately leaves the victim in a state of depression and chronic helplessness. This concept is derived from the English term